Joint position statement of the International Federation of Sports Medicine (FIMS) and European Federation of Sports Medicine Associations (EFSMA) on the IOC framework on fairness, inclusion and non-discrimination based on gender identity and sex variations. Issue 1 (18th January 2022) - Pigozzi, Fabio; Bigard, Xavier; Steinacker, Juergen; Wolfarth, Bernd; Badtieva, Victoriya; Schneider, Christian; Swart, Jeroen; Bilzon, James Lee John; Constantinou, Demitri; Dohi, Michiko; Di Luigi, Luigi; Fossati, Chiara; et al.
Abstract : The IOC recently published its framework on fairness, inclusion and non-discrimination based on gender identity and sex variations. This framework is drafted mainly from a human rights perspective, with less consideration for medical/scientific issues. The framework places the onus for gender eligibility and classification entirely on the International Federations (IFs), even though most will not have the capacity to implement the framework. The position of no presumption of advantage is contrary to the 2015 IOC consensus. Implementation of the 2021 framework will be a major challenge for IFs that have already recognised the inclusion of trans and women athletes with differences of sexual development (DSD) using a scientific/medical solution. The potential consequences for sports that need to prioritise fairness or safety could be one of two extremes (1) exclusion of all transgender or DSD athletes on the grounds of advantage or (2) self-identification that essentially equates to no eligibility rules. Exclusion of all transgender or DSD athletes is contrary to the Olympic charter and unlawful in many countries. While having no gender eligibility rules, sport loses its meaning and near-universal support. Athletes should not be under pressure to undergo medical procedures or treatment to meet eligibility criteria. However, if an athlete is fully informed and consents, then it is their free choice to undergo carefully considered or necessary interventions for gender classification for sport to compete fairly and safely in their chosen gender. Free choice is a fundamental human right, but so is the right to fair and safe competition.